Dryland Agronomic Research of ICARDA - Devkota Wasti, Mina Kumari (International Center for Agricultural Research in the Dry Areas, 2022)
Drylands cover 40% of the world’s land area and support 2 billion people – 90 % are living in developing countries. At the same time, crop production in dryland has several challenges and is most affected by the variable climate (mainly rainfall variability and temperature extreme) and climate change than any other region in the globe. For sustaining agriculture production in rainfed drylands it is important to adopt agriculture practices including crops and crop varieties and management practices that are resilient and produce stable yields in such climatic conditions. International Centre for Agriculture Research in the Dry Areas (ICARDA) has been working on several research and development activities with a major focus on dryland agriculture in the last 45 years. This presentation highlights the ICARDA’s s major agronomic research and its implication on crop productivity and resource use efficiency for dryland cereal production which are more suitable in the context of Turkey’s rainfed drylands.